Opening a Window on Attention: Adjuvant Therapies for Inflammatory Bowel Disease - Qiyue Wang; Shuyi Mi; Zixuan Yu; Qiyi Li; Jiacai Lei (Canadian Journal of Gastroenterology and Hepatology)
Inflammatory bowel disease (IBD), most commonly known as Crohn’s disease (CD) and ulcerative disease (UC), is a chronic and relapsing intestinal disease which cannot be cured completely. The prevalence of IBD in Europe and in North America has increased over the past 20 years. As most IBD patients are young at onset, their quality of life (QOL) can be influenced to varying degrees. Thus, current treatment goals are typically focused on preventing complications, including maintaining clinical remission and improving the QOL. Adjuvant therapies have been widely concerned as an effective treatment in alleviating IBD symptoms, including dietary intervention, traditional Chinese medicine, smoking, alcohol, and physical activities. This review focuses on different ancillary therapies for IBD treatments, in particular the mechanism of reducing inflammation based on the actual data from research studies. Moreover, comparing the latest data, this review also presented potential future prospect for adjuvant therapies.